ANALISIS DIKSI DAN GAYA BAHASA METAFORIS DALAM LIRIK LAGU ALBUM "LELAKU" OLEH FOURTWNTY (KAJIAN STILISTIKA) - Kamilata, Izzun; Sariban; Irmayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of diction and metaphorical language in the lyrics of Fourtwnty’s Lelaku album through a stylistic approach. The research employed a qualitative descriptive method. The data consisted of song lyrics from three tracks in the Lelaku album, namely Aku Tenang, Diam-Diam Kubawa 1, and Hitam Putih. Data were collected through listening, reading, and note-taking techniques, and analyzed through identification, classification, interpretation, and conclusion-drawing stages. The analysis of diction was based on Keraf’s theory of diction, while metaphorical language was examined from a stylistic perspective. The findings reveal that the lyrics contain various forms of diction, including connotative diction, denotative diction, general words, specific words, scientific terms, and popular words. Connotative diction emerged as the most dominant category, serving to convey symbolic and reflective meanings. Furthermore, the lyrics employ several types of metaphorical language, including anthropomorphic metaphors, synesthetic metaphors, and concrete-to-abstract metaphors, whereas animal metaphors were not identified. The integration of diction and metaphor constructs Fourtwnty’s distinctive stylistic identity, characterized by poetic expression, contemplation, and existential reflection.